Клінічні прояви ураження серцево-судинної системи у хворих на гіпотиреоз - Зелінська, Н. Б. (Clinical Endocrinology and Endocrine Surgery, 2008)
In the article frequency of clinical manifestations of cardio-vascular system involvement is studied in hypothyroid patients. Dependence of frequency and degree of expressed manifestations is analyzed depending on age of patients, severity of hypothyroidism, its duration and state of compensation. The special attention is spared the state of blood pressures